Text as a verbalized consciousness in expert analysis - Shevchenko, Larysa; Syzonov, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2020)
The article is devoted to a complex set of issues related to the understanding of the TEXT category in modern jurisprudence and practical activities of an expert linguist. According to the authors of the article, the text as a verbalized consciousness of an individual / a social group / people has integral features inherent in verbal communication of homo sapiens, such as internal coherence, logic, completeness, linguistically represented formal realization, etc. However, the text as an object of linguistic expertise is a complex communicative substance, formalized in words (written / graphic), sounds (oral), words and sounds (creolized). Therefore, the criteria for reference to the text are its semantic and grammatical connection, which are manifested in the systematic and consistent completion of linguistic communication. The characteristics of the text in the linguistic-expert analysis are correlated with the communicative sphere of functioning – mass media, fictional, official business, scientific, which is analyzed by the linguist-expert in the corresponding stylistic categories. Hence, linguists-experts analyze the communicative parameters of the text in terms of cohesion, coherence, semantic decoding, possibilities of perception by recipients, informativeness, hyper- and intertextuality, manipulativeness. The questions posed to the linguist-expert are specified by the specialist only when analyzing the proposed text, which provides for its professional separation from other similar verbalized communicative structures. The article pays special attention to the distinction between such concepts of legal linguistics as "linguistic expertise", "linguistic legal expertise", "judicial expertise", "linguistic expertise of a legal text" which are key in the professional work of a linguist-expert. Thus, the text, correlated with the linguistic consciousness of the author, appeals to the recipient, is determined in the systemic characteristics of a particular functional style and communicative situation.
Keywords: text as verbal consciousness; text characteristics; linguistic expert analysis; linguistic expertise; legal linguistics.